Computer self efficacy: teacher readiness in accepting Malaysian EduwebTV - Ismail, Mohd Arif; Mahmud, Rosnaini; Mohd Nor, Noraini; Ahmad, Jamil; Abd Rahman, Mohd Jasmy (IDOSI Publications, 2011)
The role of Library and Media Teacher (LMT) as a catalyst for the implementation to the technology programs conducted in schools is a challenge to the LMT which is to be more open and innovative towards innovations introduced in schools from time to time. This study is to determine the level of computer self-efficacy (CSE) of the Library and Media Teacher (LMT) and to see its relations with the acceptance of EduwebTV a new innovation that has been implemented. The study involved 546 respondents of Library and Media Teacher; randomly selected from four states in Malaysia. The findings showed that the level of computer self-efficacy (CSE) of the LMT to use the EduwebTV is moderate compare to their confidence to disseminate the EduwebTV innovation. The analysis also showed a positive correlation to the perceived ease of use and perceived usefulness in acceptance of EduwebTV innovation. From these findings we can conclude that the computer self-efficacy of teachers may help to influence their perception of ease of use and usefulness of EduwebTV where it is important in this process of innovation acceptance. Computer self-efficacy has a strong positive relationship to the perception of ease of use of the EduwebTV and the perception of usefulness of the EduwebTV. This means that the higher computer self efficacy of a teacher, the easier they accept the EduwebTV. Hence the computer self-efficacy can be regarded as the basic needs of technology acceptance as it can provide positive control of the stimulus.